Mangrove ecosystem in North Sumatran (Indonesia) forests serves as a suitable habitat for mud crabs (Scylla serrata and S. olivacea) - RIKA KARNIATI; NURDIN SULISTIYONO; RIZKA AMELIA; BEJO SLAMET; YUNTHA BIMANTARA; Mohammad Basyuni (Society for Indonesian Biodiversity, 2021)
Abstract. Karniati R, Sulistiyono N, Amelia R, Slamet B, Bimantara Y, Basyuni M. 2021. Mangrove ecosystem in North Sumatran (Indonesia) forests serves as a suitable habitat for mud crabs (Scylla serrata and S. olivacea). Biodiversitas 22: 1489-1496. Mud crabs (Scylla serrata and Scylla olivacea) are often found in muddy substrates associated with mangrove vegetation. The habitat of these crabs ranges from tropical estuaries to sheltered subtropical areas, riverbanks, lower river traits, and intertidal areas. These crabs have an important economic value, and it increases the income of the communities living around the mangrove area. This study aims to obtain more information on the environmental factors of habitat for mud crabs (S. serrata and S. olivacea): insights on the effects of abiotic and biotic factors and potential economic value, in the village of Lubuk Kertang, Langkat, North Sumatra, Indonesia. Data were collected by measuring abiotic factors (temperature, pH, salinity, dissolved oxygen, mud depth, distance from the river) and biotic factors (mangrove stand density through canopy cover). The dataset was analyzed using a binary logistic regression analysis with a stepwise method. Results showed that the abiotic factors that contributed to the presence of the mud crab were dissolved oxygen and a mud depth of 68.7%. Meanwhile, the remaining 31.3% that contributed to the presence of mud crabs were abiotic factors (temperature, pH, salinity, distance from rivers) and biotic factors (stand density through canopy cover). The present study suggests that dissolved oxygen and mud depth have an important function in predicting the presence of mud crabs.